2014
DOI: 10.1177/0148607114546374
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Supplementation Induces Arginase Activity and Inhibits TNF‐α Synthesis in Mice Spleen Macrophages After Intestinal Obstruction

Abstract: Arginine supplementation and iNOS inhibition led to increased arginase activity. Arginine availability decreased plasma TNF-α levels, which may be directly related to nitric oxide derived from arginine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Therefore, the ROS-scavenging property of Arg together with its ability to sustain spare endogenous antioxidants and decrease activity of the hepatic lipogenic enzyme may inhibit oxidative liver damage and decrease inflammation status [ 6 , 47 , 52 ]. Recent studies were reported that Arg inhibits uncontrolled synthesis of TNF-α thus block its deleterious effects [ 53 , 54 ]. The experimental study of Ozsoy et al (2011) [ 55 ] demonstrated that i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ROS-scavenging property of Arg together with its ability to sustain spare endogenous antioxidants and decrease activity of the hepatic lipogenic enzyme may inhibit oxidative liver damage and decrease inflammation status [ 6 , 47 , 52 ]. Recent studies were reported that Arg inhibits uncontrolled synthesis of TNF-α thus block its deleterious effects [ 53 , 54 ]. The experimental study of Ozsoy et al (2011) [ 55 ] demonstrated that i.p.…”
Section: Discussionmentioning
confidence: 99%
“…It was also able to inhibit the production of pro-inflammatory mediator (tumor necrosis factor-α (TNF-α)) in mice spleen macrophages after intestinal obstruction (Quirino et al, 2014), as well as to improve the production of NO in diabetic-obese rats (Breuillard et al, 2012). Nevertheless, it was discovered that L-arginine promotes cardiac and muscle fibrosis in muscular dystrophy via the regulation of macrophage metabolism (Wehling-Henricks et al, 2010), and it serves as a potential pro-inflammatory agent in mice peritoneal macrophages (Pekarova et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has been proven that regular exercise training decreases inflammatory cytokines 38 . Likewise, Quirino et al (2014) showed L-arginine inhibits uncontrolled synthesis of TNF-α thus block its deleterious effects 39 . It is likely that anti-inflammatory cytokine (IL-10)-mediated upregulation of anti-oxidant defenses (such as Cu/ZnSOD) via Nrf2 may represent the underlying mechanism for exercise-induced reduction of oxidative stress 40 .…”
Section: Discussionmentioning
confidence: 99%